Content of selected polyphenolic substances in parts of grapevine - Jurasova, Lenka; Jurikova, Tunde; Baron, Mojmir; Sochor, Jiri (Italian Journal of Food Science, 2023)
This review provides an overview of the variety of occurrences, content, extraction and health effects of selected polyphenolic compounds associated with different parts of grapevine (seeds, peel, pulp and stems). The review provides a brief characterisation of grape parts, the content of polyphenolic compounds and their extraction together with their graphical forms of presentation and diversity as determined by different studies. The content of individual polyphenolic compounds differed with studies. Effects of different factors were evident in both growing style and geographical location of vineyards as well as extraction methods and analytical conditions.